Travel Intention of Muslim Tourist to Visit Non-Muslim Country: A Conceptual Paper of Extended Theory of Planned Behavior (ETPB) - noveri maulana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper is aimed to analyze the theoretical concept of travel intention of Muslim tourists to visit Non-Muslim countries as their traveling destination. Using the Extended Theory of Planned Behavior (ETPB), this research is implementing three additional variables as the antecedents of TPB which are Religiosity, Materialism, and Destination Image. Several hypotheses are proposed to analyze the impact of those additional variables toward the Muslim travel intention to visit the non-Muslim countries. This conceptual paper will contribute to the development of future empirical research regarding the implementation of TPB in the Halal Tourism context.